Profil Kitab Tafsir, Model Pemahamannya Pengaruhnya Terhadap Fiqih Ibadah Pada Pondok Pesantren Di Provinsi Riau - Erman Gani (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
Pondok Pesantren (classical Islamic educational institution in Indonesia) uses the classic book strictly and continuously. Students (santri) fanatically follow the book used by the teacher, including in the use of the book of exegesis. Pondok Pesantren in Riau Province uses the book of tafsir differently according to the grouping of the tradition and the teacher's understanding of the Pondokmya. Most of the Pondok Pesantren in Riau Province, using a translation book that is not a yellow book (Arabic Book. This situation tends to eliminate the character of Pondok Pesantren which makes the yellow book (Arabic Book) as the basis and its main characteristic. This paper seeks to see the profile of the book of tafsir, model of understanding and that’s correlation according to relegius jurisprudence on Pondok Pesantren in Riau Province.